About Sarah Oates and her neo-soviet media model. Preface by the scientific editor of the translation (Herald of Journalism, 2023)
The reader is offered for the first time the translation of Sarah Oates' program article "The Neo-Soviet Media Model", published in 2007 (Sarah Oates, 2007). In the preface by the scientific editor of the translation, the relevance of the publication is substantiated. The theoretical context of the article’s appearance is characterized, including the scientific discussion about the normative theories of media in the mid-2000s. The goal of the scientific reflection is to offer a critical eye at the research methodology of Sarah Oates, as well as a number of comments on the transformation of the Russian media system over the 16 years after the publication of the article. This article has two parts: preface by the scientific editor and direct translation of the article by Sarah Oates "The Neo-Soviet Model of Media".As annotated by Sarah Oates, the article “explores the genesis of the neo-Soviet media model. Based on the results of the study of Russian media in the post-Soviet period, as well as a review of their activities during elections in the above region, the article concludes that Russian media currently operate in a "neo-Soviet" manner. Factors shaping this media model include the rejection of a balanced approach or objectivity; the presence of flaws in the legislation regulating the activities of the media; self-censorship; state interference and pressure on the media; lack of professionalism in the journalistic environment; and an atmosphere of violence against journalists. Furthermore, in the transition from the Soviet to the neo-Soviet model, there is continuity in how the media are perceived by their audience.”Keywords: Sarah Oates, neo-Soviet media model, media system, censorship, post-Soviet space, content analysis.